Rhodium(III)-Catalyzed Regioselective C7-Allylation of Indazoles - Huo, Jiyou; Yuan, Hongshun; Xu, Lanting; Pan, Xianhua (Synlett, 2020)
An efficient rhodium-catalyzed regioselective C–H allylation of N,N-diisopropylcarbamoyl indazoles with allylic carbonates as allylating agents has been developed. This methodology provides facile access to C7-allylated indazoles with high regioselectivity, ample substrate scope and broad functional group tolerance.
Keywords: indazoles; C–H activation; regioselectivity; allylation; rhodium catalysis